The Relationship Between Parental Verbal Abuse and Self Esteem in Adolescent at Junior High School 4 Jember - Maulida Litasari; Peni Perdani Juliningrum; Eka Afdi Septiyono (Universitas Bondowoso, 2022)
Introduction: Verbal abuse was a form of abuse by saying words or sentences that are negative such as insult, humiliate, refuse, yell, or berate has an impact on the development of adolescent self-esteem. Self-esteem was a self-assessment that is influenced by attitude, interaction, award, and form of acceptance of others towards an individual. This study aim was to determine the relationship between parental verbal abuse and self-esteem in adolescents. Method: The research design used quantitative methods with a correlation design and a cross-sectional approach. The sampling technique used simple random sampling to obtain a sample of 152 students from the calculation of the Slovin formula.Data collection used a questionnaire and the statistical test used Chi-square. Result: The result showed that verbal abuse committed by parents was 93%, self-esteem in adolescents obtained high self-esteem results of as much as 89%, and there was no relationship between the variables of parental verbal abuse and self-esteem in adolescents with a p-value of 0,0246. Conclusion: The absence of a relationship between the variable verbal abuse and the variable self-esteem occurs because adolescents in developmental tasks seek identity and improve self-integrity. So that adolescents will spend more time with friends and their relationship with their parents will be stretched.